Spatio-Temporal Color Differences Between Urban and Rural Populations of a Ground Beetle During the Last 100 Years - Keinath, Silvia; Frisch, Johannes; Müller, Johannes; Mayer, Frieder; Rödel, Mark-Oliver (Frontiers in Ecology and Evolution, 2020)
Increasing anthropogenic environmental impacts lead to rapid transitions of ecosystems and species. Species persisting in changing environments may respond to changes by altering phenotypic traits across space and/or time. Here we tested whether the frequencies of three color morphs in the ground beetle Harpalus affinis differed across spatial and temporal gradients. The gradients extended from urban to rural regions, and from the early 20th century until today, in the Berlin-Brandenburg area, Germany. Specimens comprised beetles from the entomological collection of the Museum für Naturkunde, Berlin and recently collected material. As a result of differing environments, we expected to observe differences in color frequencies in beetles between habitats and across time, responding to different levels of urbanization. Our results revealed sexual dichromatism in H. affinis as well as some habitat dependent differences in trait frequency. Frequencies of color morphs remained generally constant in males across space and time. Females likewise showed no differences in color frequencies between habitats, urban and rural regions, and between different time periods in rural regions. In contrast color morph frequencies changed in urban regions over time in females: Bronze color decreased, whereas green color became more dominant over time. We assume that bronze color was selectively advantageous in times with high levels of soot pollution in the city, whereas green is more cryptic and thus advantageous in times with less polluted air. The color change of females thus could have been driven by natural selection. In contrast, the persistence of predominately green males through all times and habitats, more likely can be explained by sexual selection.